Intracultural Philosophy: Exploring the Splendour of The Interconnectedness among the Branches of Philosophy And its Relevance for 21st Century Philosophy - Uzoigwe, Elias Ifeanyi; Sanga, Innocent (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
The main thrust of this study is on the interconnectedness among the branches and sub-branches of philosophy. This synergy is not only indispensable, but relevant to the evolution and advancement of 21st century philosophy. Epistemology, metaphysics, ethics, logic, and aesthetics form the foundation of philosophical inquiry, while sub-branches such as socio-political philosophy, philosophy of mind, philosophy of science, philosophy of religion, philosophy of mathematics, and a host of others offer specialised insights into human existence, knowledge, morality, and reality in general. The dynamic interaction among these branches and sub-branches of philosophy, which we call intracultural philosophy, enriches philosophical discourse and allows for dialogue and intradisciplinary engagement. For example, epistemology and ethics intersect in areas like bioethics, while metaphysics and logic converge in debates about free will and identity. Similarly, aesthetics and political philosophy synergise in analysing the ethical impact of art and beauty in society. As it were, 21st century philosophy is increasingly influenced by applied philosophy, addressing practical concerns such as biodiversity, climate change, artificial intelligence (AI), environmental ethics, gender studies, and global justice. Philosophical pluralism, incorporating both African and Western perspectives broadens the scope of contemporary thought, fostering a more inclusive global dialogue for interculturally oriented intellectual exchange. Furthermore, advancements in technology introduce novel epistemological and ethical insights and challenges, compelling philosophers to revisit classical questions vis-à-vis modern developments. The critique of traditional metaphysics by deconstructionist-postmodern thinkers further complicates and enriches the interconnectedness, questioning foundational assumptions and encouraging new modes of inquiry, and this is indeed, part of the splendour of the intraculturality among the branches and sub-branches of philosophy.